Vaginal delivery versus cesarean section for term breech delivery - Babović Ivana; Plešinac Snežana; Radojičić Zoran; Opalić Jasna; Argirović Rajka; Mladenović-Bogdanović Zorica; Plećaš Darko (Vojnosanitetski Pregled)
Background/Aim. The optimal method of delivery for breech presentation at term still remains a matter of controversy. This is probably due to the fact that the skills of vaginal breech delivery are being lost. The aim of this study was to examine risk factors: mother's age, parity, labor's duration, estimated neonatal birth weight for the mode of breech presentation delivery at term as well as the influence of the delivery mode on neonatal outcome. Methods. A retrospective study of 401 terms (more than 37 week's gestation) breech deliveries at the Institute of Gynecology and Obstetrics, Belgrade, from 2007 to 2008 was made. The following groups with respect to mode of delivery were included: the group I - vaginal delivery (VD) in 139 patients; the group II - urgent cesarean section (UCS) in 128 patients; and the group III - elective cesarean section (ECS) in 134 patients. Mother's age, parity, duration of VD, neonatal birth weight (BW), the Apgar score at 5th minute, and duration of stay in a neonatal intensive care unit (NICU) vere determined. Neonatal mortality and major neonatal morbidity were compared according to the route of delivery. Fetuses and neonates with hemolytic disease and fetal and neonatal anomalies were excluded from the study. For statistical analyses we performed Student's t test, χ2 likelihood ratio, Kruskall-Wallis test, Mann Whitney test, and ANOVA. Results. The mean age of patients in the group I was 28.29 ± 4.97 years, in the group II 29.68 ± 5.92 years and in the group III 30.06 ± 5.41 years. Difference in mother's age between the group I and III was significant (p = 0.022). In the group III there were 73.9% nuliparous similarly to the gropu II (73.4%). We performed ECS in 54.6% of the nuliparous older than 35 years, and 54.4% multiparous younger than 35 years were delivered by VD. The use of oxytocin for stimulation of vaginal labor was not associated with its duration (p = 0.706). Lowset maneuver was performed in 88.5% of the VD. Mean BW of neonantes was 3189.93 ± 399.42 g in the VD group, 3218.59 ± 517.71 g in the UCS and 3427.99 ± 460.04 g in the ECS group. Neonates of the estimated BW below 2 500 g were delivered by UCS in 5.5% cases, vaginally in 3.6% cases and by ECS in 2.2% cases. Neonates of the estimated BW above 3 500 g were delivered by ECS in 44.8% cases, vaginally in 23.0% cases and by UCS in 30.5% cases. There was a statistically significant difference between the VD and UCS groups (p = 0.004). Neonatal well-being was diagnosed in 75.5% of the neonates in the VD group, in 72.4% of the neonates in the ECS group, and in 65.5% of the neonates in the UCS group. The Apgar score at 5th min ≥ 8 was observed in 96% of the neonates in the VD group, in 97.5% of the neonantes in the ECS group and in 94.5% of the neonantes in the UCS group. In breech presentation, perinatal asphyxia remained increased in the VD group by 9.4% as compared with the UCS group, 5.5% (p = 0.001) and the ECS group, 3.0% (p = 0.016). Neonates stayed in NICU significantly longer after UCS compared with VD or ECS (7.21 ± 10.74 days vs 3.99 ± 1.33 days and 5.34 ± 2.88 days, respectively; p = 0.001 and p = 0.037, respectively). There was no diagnosed intracranial hemorrhage, brachial plexus injury and birth trauma in any groups. Also, there was no early neonatal death. Conclusion. For breech presentation elective cesarean section remains the major delevery method in nuliparous older than 35 years, while vaginal delivery is considered to be the method of choice in younger multiparous with ultrasonographically estimated neonatal birth weight 2 500-3 500 grams.